Dingo boy - Dugan, Michael, 1947-2006. (Ringwood, Vic. : Kestrel Books, 1980)
A fourteen-year-old orphan is fostered by a farmer who uses him as unpaid labour until Carl realizes he has to make a stand.
For children.
White, K. Bibliography of Australian children's books
Keywords: Children's stories in English. Australian writers, 1945-. Texts; Orphans -- Australia -- Juvenile fiction; Dingo -- Juvenile fiction; Farm life -- Australia -- Juvenile fiction; Maturation (Psychology) -- Juvenile fiction